Decarceration from Local County Jails during the COVID-19 Pandemic: A Closer Look. Issue 5 (20th October 2022) - Martyn, Kevin P.; Andel, Stephanie; Stockman, M. Rhebeca N.; Grommon, Eric
ABSTRACT: The COVID-19 pandemic initially compelled population reductions at local county jails. This study uses daily population counts at 970 jail facilities in 43 different U.S. states to; assess changes in jail population levels during 2020; relate those changes to the demographic, economic, and political characteristics of the counties where they took place; and examine the relationships between jail population levels and COVID-19 cases and deaths. Jail population data was gathered by the Jail Data Initiative at New York University and linked to other publicly accessible data collections. Through descriptive analyses and latent growth curve modeling, our findings indicate that while jail population levels generally fell in the early stages of the pandemic, they remained higher in areas with larger proportions of minoritized populations, and returned more rapidly to pre-pandemic levels in areas with larger proportions of Black and Republican-leaning residents. Larger pre-pandemic jail population rates were associated with elevated COVID-19 case and death rates during 2020, and changes in local jail population rates predicted case and death rates over a following three-month period. Specifically, each percentage increase in jail populations was associated with between 80.4 and 101.9 additional cases and 1.2 to 1.4 additional deaths per 10 K county residents.